2021
DOI: 10.1111/appy.12488
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the trends of polypharmacy and high‐dose prescriptions in Japan

Abstract: Introduction After extensive research, this study explored whether high‐dose prescriptions and polypharmacy remain more frequent in Japan than elsewhere. If confirmed, we aimed to identify the factors that contributed to this unique trend. Methods The psychotropic drug prescription patterns for patients with schizophrenia in Japan were reviewed. This was based on a large sample collected from surveys of the Research on Asian Psychotropic Prescription Patterns, an international collaborative research project co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…The proportion of antipsychotic polypharmacy was not different between decades; however, regarding regions, the prevalence was higher in Asia and Europe than in North America. Research on Asian Psychotropic Prescription Patterns in 2016 examined the proportion of polypharmacy in patients with schizophrenia among 15 countries and areas in Asia 43 . These data demonstrated a continued declining trend of antipsychotic polypharmacy in Japan; however, Japan continued to demonstrate the highest proportion of polypharmacy and highest dosages of psychotropic prescription drugs in Asia 43 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of antipsychotic polypharmacy was not different between decades; however, regarding regions, the prevalence was higher in Asia and Europe than in North America. Research on Asian Psychotropic Prescription Patterns in 2016 examined the proportion of polypharmacy in patients with schizophrenia among 15 countries and areas in Asia 43 . These data demonstrated a continued declining trend of antipsychotic polypharmacy in Japan; however, Japan continued to demonstrate the highest proportion of polypharmacy and highest dosages of psychotropic prescription drugs in Asia 43 .…”
Section: Discussionmentioning
confidence: 99%
“…43 Although a polypharmacy reduction policy by the government, which reduces the reimbursement of medical costs, was introduced in 2014 and 2016, it seems to be insufficient. 43 National mental health policies based on hospitals and financing systems might be obstacles to reducing polypharmacy in Japan. The severity of major depressive disorder and polypharmacy in 44 000 patients in Europe from 2001 to 2017 suggests a trend toward polypharmacy depending on severity; however, changes in polypharmacy over time were not reported.…”
Section: Pcn Psychiatry Andmentioning
confidence: 99%
“…In addition, psychiatrists may tend to conduct multi-psychotropic drug prescriptions because an association between psychiatrists and multi-psychotropic drug prescription or polypharmacy are shown in other countries [45][46][47]. Moreover, it is mentioned in a previous study that factors, such as physician's culture, patient's attitude, and lack of training in psychopharmacology are possible reasons why psychiatrists in Japan continue to prescribe multiple drugs and high doses of psychotropics compared with other countries [1].…”
Section: Discussionmentioning
confidence: 99%
“…Polypharmacy is one of the most frightening public health problems worldwide [1,2]. In Japan over the past few years, the prevalence of polypharmacy has decreased [3,4], while the prevalence of potentially inappropriate medications has increased [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, according to a survey using a large-scale health insurance claims database conducted in 2021 by Takeshima et al, the mean duration of hypnotic prescriptions was 2.9 months, and 9.3% of patients were prescribed hypnotics for 12 months [ 11 ]. Moreover, an observational study using a Japan Medical Data Center dataset containing all medical fee data of health insurance service subscribers from 2015 to 2019 showed that the prescription of high-potency hypnotics (>15 mg/day diazepam) and anxiolytics (>2 mg/day flunitrazepam) generally remained unchanged [ 12 ]. These results suggest that the Japanese policies did not significantly affect long-term and high-dose BZD use.…”
Section: Introductionmentioning
confidence: 99%